Making Sense of Corporate Social Responsibility (CSR) at Enterprise - Vigneau, Laurence (2010)
This dissertation examines the internal construction of a corporate social responsibility (CSR) identity at a car rental company, Enterprise. It is based on an interpretive single-case study of Enterprise East Midland office and branches. The study was conducted through a research placement at Enterprise, where I was able to conduct semi-structured interviews and have access to internal and external documentation. The aim of this dissertation is to describe, compare and interpret the managers’ and employees’ construction of a CSR identity. I co-constructed the managers and employees CSR identity narratives and analysed them with regard to the literature on organizational identity, sensemaking/sensegiving and legitimacy. This led me to better understand how employees and managers make sense of and give sense to CSR. It also helped me grasp the notions of control and legitimacy around CSR at Enterprise. The dissertation’s goal is to produce insight on Enterprise’s CSR identity and suggest possible actions for Enterprise to tackle some issues related to the internal perceptions of CSR. The study shows that employees constructed a different CSR identity from the managers. A sensegiving problem was identified, as managers were not able to transmit the morality argument of CSR to employees. This study also highlights the role of internal communication in the sensegiving processes around CSR at Enterprise, as well as the influence of organizational identity on CSR identity.